Heterostuctures of 4-(chloromethyl)phenyltrichlorosilane and 5,10,15,20-tetra(4-pyridyl)-21H,23H-porphine prepared on Si(111) using particle lithography: Nanoscale characterization of the main steps of nanopatterning - Chambers, Phillip C.; Garno, Jayne C. (Beilstein Journal of Nanotechnology, 2018)
Nanostructures of 4-(chloromethyl)phenyltrichlorosilane (CMPS) were used as a foundation to attach and grow heterostructures of porphyrins and organosilanes. A protocol was developed with particle lithography using steps of immersion in organosilane solutions to selectively passivate the surface of Si(111) with octadecyltrichlorosilane (OTS). A methyl-terminated matrix was chosen to direct the growth of CMPS nanostructures to fill the uncovered sites of Si(111) to enable spatial confinement of the surface reaction. Silica spheres with a diameter of 500 nm were used as a surface mask to prepare nanoscopic holes within the OTS matrix film. Next, the samples were immersed in solutions of CMPS dissolved in toluene or bicyclohexane. Nanostructures of CMPS formed within the nanoholes, to furnish spatially selective sites for binding porphyrins. The samples were then characterized with AFM to evaluate the height and morphology of the CMPS nanostructures that had formed within the nanoholes of OTS. The samples were then refluxed in a porphyrin solution for selective binding to produce heterostructures. The attachment of porphyrins was evidenced by increases in the height and width of the CMPS nanopatterns. The measurements of size indicate that multiple layers of porphyrins were added. Through each step of the surface reaction the surrounding matrix of OTS showed minimal areas of nonspecific adsorption. The AFM studies provide insight into the mechanism of the self-polymerization of CMPS as a platform for constructing porphyrin heterostructures.
Keywords: atomic force microscopy (AFM); nanostructures; particle lithography; porphyrin; self-assembly

(untitled) - Auwärter, W.; Écija, D.; Klappenberger, F.; Barth, J. V. (Nat. Chem., 2015)

(untitled) - Li, D.; Swanson, B. I.; Robinson, J. M.; Hoffbauer, M. A. (J. Am. Chem. Soc., 1993)

(untitled) - Li, D.; Buscher, C. T.; Swanson, B. I. (Chem. Mater., 1994)

Metal-Containing and Metallosupramolecular Polymers and Materials - Garno, J. C.; Xu, C.; Bazzan, G.; Batteas, J. D.; Drain, C. M. (Designing Supramolecular Porphyrin Arrays for Surface Assembly and Patterning of Optoelectronic Materials, 2006)

(untitled) - Cai, J.; Chen, H.; Huang, J.; Wang, J.; Tian, D.; Dong, H.; Jiang, L. (Soft Matter, 2014)

(untitled) - Bai, F.; Sun, Z.; Wu, H.; Haddad, R. E.; Coker, E. N.; Huang, J. Y.; Rodriguez, M. A.; Fan, H. (Nano Lett., 2011)

(untitled) - Miller, J. S. (Adv. Mater., 1998)

(untitled) - Alivisatos, P.; Barbara, P. F.; Castleman, A. W.; Chang, J.; Dixon, D. A.; Klein, M. L.; McLendon, G. L.; Miller, J. S.; Ratner, M. A.; Rossky, P. J.; Stupp, S. I.; Thompson, M. E. (Adv. Mater., 1998)

(untitled) - Senge, M. O.; Fazekas, M.; Notaras, E. G. A.; Blau, W. J.; Zawadzka, M.; Locos, O. B.; Ni Mhuircheartaigh, E. M. (Adv. Mater., 2007)

(untitled) - Benítez, I. O.; Bujoli, B.; Camus, L. J.; Lee, C. M.; Odobel, F.; Talham, D. R. (J. Am. Chem. Soc., 2002)

(untitled) - Zhai, X.; Alexander, D.; Derosa, P.; Garno, J. C. (Langmuir, 2017)

(untitled) - Zhai, X.; Arachchige, N. M. K. K.; Derosa, P.; Garno, J. C. (J. Colloid Interface Sci., 2017)

(untitled) - Kanaizuka, K.; Izumi, A.; Ishizaki, M.; Kon, H.; Togashi, T.; Miyake, R.; Ishida, T.; Tamura, R.; Haga, M.-a.; Moritani, Y.; Sakamoto, M.; Kurihara, M. (ACS Appl. Mater. Interfaces, 2013)

(untitled) - Lepper, M.; Kobl, J.; Schmitt, T.; Gurrath, M.; de Siervo, A.; Schneider, M. A.; Steinruck, H.-P.; Meyer, B.; Marbach, H.; Hieringer, W. (Chem. Commun., 2017)

(untitled) - Albrecht, F.; Bischoff, F.; Auwärter, W.; Barth, J. V.; Repp, J. (Nano Lett., 2016)

(untitled) - Lu, X.; Hipps, K. W.; Wang, X. D.; Mazur, U. (J. Am. Chem. Soc., 1996)

(untitled) - Lei, S.-B.; Deng, K.; Yan-Lian, Y.; Zeng, Q.-D.; Wang, C.; Jiang, J.-Z. (Nano Lett., 2008)

(untitled) - Bearinger, J. P.; Stone, G.; Christian, A. T.; Dugan, L.; Hiddessen, A. L.; Wu, K. J. J.; Wu, L.; Hamilton, J.; Stockton, C.; Hubbell, J. A. (Langmuir, 2008)

(untitled) - Bearinger, J. P.; Stone, G.; Dugan, L. C.; El Dasher, B.; Stockton, C.; Conway, J. W.; Kuenzler, T.; Hubbell, J. A. (Mol. Cell. Proteomics, 2009)

(untitled) - Vesper, B. J.; Salaita, K.; Zong, H.; Mirking, C. A.; Barrett, A. G. M.; Hoffman, B. M. (J. Am. Chem. Soc., 2004)

(untitled) - Chen, X.; Lei, S.; Lotze, C.; Czekelius, C.; Paulus, B.; Franke, K. J. (J. Chem. Phys., 2017)

(untitled) - Samori, P.; Engelkamp, H.; de Witte, P. A. J.; Rowan, A. E.; Nolte, R. J. M.; Rabe, J. P. (Adv. Mater., 2005)

(untitled) - Shimadzu, T.; Segawa, H.; Wu, F.; Nakayama, N. (J. Photochem. Photobiol., A, 1995)

(untitled) - Holten, D.; Bocian, D. F.; Lindsey, J. S. (Acc. Chem. Res., 2002)

(untitled) - Saner, C. K.; Lusker, K. L.; LeJeune, Z. M.; Serem, W. K.; Garno, J. C. (Beilstein J. Nanotechnol., 2012)

(untitled) - Saner, C. K.; Lu, L.; Zhang, D.; Garno, J. C. (Nanotechnol. Rev., 2015)

(untitled) - Hulteen, J. C.; Van Duyne, R. P. (J. Vac. Sci. Technol., A, 1995)

(untitled) - Bae, C.; Shin, H.; Moon, J.; Sung, M. M. (Chem. Mater., 2006)

(untitled) - Deckman, H. W.; Dunsmuir, J. H. (Appl. Phys. Lett., 1982)

(untitled) - Li, J.-R.; Garno, J. C. (Nano Lett., 2008)

(untitled) - Lusker, K. L.; Yu, J.-J.; Garno, J. C. (Thin Solid Films, 2011)

(untitled) - Jensen, T. R.; Malinsky, M. D.; Haynes, C. L.; Van Duyne, R. P. (J. Phys. Chem. B, 2000)

(untitled) - Haynes, C. L.; Van Duyne, R. P. (J. Phys. Chem. B, 2001)

(untitled) - Lewandowski, B. R.; Kelley, A. T.; Singleton, R.; Li, J.-R.; Lowry, M.; Warner, I. M.; Garno, J. C. (J. Phys. Chem. C, 2009)

(untitled) - Chen, J.; Liao, W.-S.; Chen, X.; Yang, T.; Wark, S. E.; Son, D. H.; Batteas, J. D.; Cremer, P. S. (ACS Nano, 2009)

(untitled) - Englade-Franklin, L. E.; Morrison, G.; Verberne-Sutton, S. D.; Francis, A. L.; Chan, J. Y.; Garno, J. C. (ACS Appl. Mater. Interfaces, 2014)

(untitled) - Chen, M.-S.; Brandow, S. L.; Schull, T. L.; Chrisey, D. B.; Dressick, W. J. (Adv. Funct. Mater., 2005)

(untitled) - Brandow, S. L.; Chen, M.-S.; Dulcey, C. S.; Dressick, W. J. (Langmuir, 2008)

(untitled) - Tian, T.; LeJeune, Z. M.; Garno, J. C. (Langmuir, 2013)

(untitled) - Chambers, P. C.; Garno, J. C. (J. Vac. Sci. Technol., B, 2018)

(untitled) - Ulman, A. (Chem. Rev., 1996)

(untitled) - Nečas, D.; Klapetek, P. (Cent. Eur. J. Phys., 2012)